The UCC Accountancy Program and the Employability of Its Graduates (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The study sought to determine the employment status and experiences of graduates of the Bachelor of Science in Accountancy program at a particular university. The findings would provide valuable insights into the program’s effectiveness in preparing students for the workforce and inform future curriculum development and career guidance initiatives.The study adopted a student-centered approach, recognizing that the ultimate goal of education is to equip students with the knowledge, skills, and competencies necessary to succeed in their chosen careers. This approach emphasizes active learning, individualized instruction, and integrating real-world experiences into the curriculum.The study employed a quantitative approach, utilizing numerical data to analyze the employment status and experiences of the graduates. A descriptive research design was chosen to provide a comprehensive overview of the data and identify key trends and patterns.The study participants were recent Bachelor of Science in Accountancy program graduates from the School of Business Sciences. This sampling frame allowed for a focused examination of the employability outcomes specific to this academic program.A modified UCC graduate study questionnaire served as the primary data collection tool. The questionnaire was adapted to gather relevant information about the graduates' employment status, job search experiences, and satisfaction with their current employment.The data collected from the questionnaire were analyzed using descriptive statistics, including frequency, percentage, and mean. These measures provided insights into the distribution of responses and the central tendency of the data.The study revealed that many Bachelor of Science in Accountancy program graduates were successfully employed within a year of graduation. Many of these graduates secured permanent employment contracts, indicating their strong employability and value to the accounting profession.The findings suggest that graduates from this program were able to find employment relatively quickly, with most securing their first job within a year of graduation. This rapid transition into the workforce highlights the program’s effectiveness in preparing students for the demands of the accounting industry.Most employed graduates worked in private-sector organizations, reflecting the strong demand for accounting professionals in this sector. However, the data indicated that many graduates were still in their first year of employment, suggesting there may be opportunities for further career advancement and specialization in the coming years.The study identified several key factors influencing the graduates' decision to choose the Bachelor of Science in Accountancy program. The university's reputation, the relevance of the program’s training to their professional aspirations, and overall quality stood out as significant factors in their decision-making process.The study recommends that future research on the employability of accountancy graduates explore their definitions of success and correlate them with their current employment profiles. This approach would provide a deeper understanding of the graduates' career aspirations and the factors that contribute to their perceived success in the accounting profession. Comparing the employability outcomes of accountancy graduates across different countries could provide valuable insights into the influence of cultural and economic factors on the demand for accounting professionals and the effectiveness of accounting education programs in preparing graduates for the global workforce.
Keywords: employabilit; BSA graduates; tracer study; outcome-based education